Polypharmacy in Geriatric Oncology - Ulusoylar N.; DOST F. S.; SOYSAL P. (My University, 2020)
The growing incidence of comorbidities related to the prolongation of life span brings out the risk of polypharmacy. Problems caused by polypharmacy could be more severe in elderly patients due to changes in the pharmacokinetics and pharmaceutical effects of drugs. Especially in elderly patients with malignant disease, new drugs are added to the list because of cancer symptoms and chemotherapy related complications. Polypharmacy leads to increased overall mortality related to increased frailty and increased number of falls and decreased quality of life and mobility in the elderly. Drug-drug and disease-drug interactions might become inevitable when herbal medications, vitamin tablets and drugs without prescription are involved. Hospital administrations and the cost of treatments also rise along with the increased number of drugs that are used. Elderly patients should be thoroughly evaluated with a multidisciplinary approach using detailed geriatric assessment tools, and drugs that are either useless or potentially harmful should be disposed along the way. Geriatritians, oncologists and especially family practitioners should give heed to the proper management and possible interactions of drugs that are used.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Onkoloji; Geriatri; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Oncology; Geriatrics; Health Sciences; Klinik Tıp; Klinik Tıp (Med); Geriatri ve Gerontoloji; Clinical Medicine; Clinical Medicine (Med); Geriatrics & Gerontology; Geriatrics and Gerontology